Concomitant wastewater treatment with lipid and carotenoid production by the oleaginous yeast Rhodosporidium toruloides grown on brewery effluent enriched with sugarcane molasses and urea. (July 2020) - Dias, Carla; Reis, Alberto; Santos, José A.L.; Lopes da Silva, Teresa
Graphical abstract: Brewery effluents supplemented with sugarcane molasses and urea were used as growth medium to develop the yeast Rhodosporidium toruloires NCYC 921, to produce triacylglicerols (TAGs) and carotenoids. The yeast cultivation was monitored by flow cytometry, in order to understand the impact of the effluent on the yeast cell membrane. Ideally the treated effluent may be discharged in the water bodies. Highlights: Brewery effluent was used to grow R. toruloides for lipids and carotenoids production. Sugarcane molasses and urea improved the yeast lipids and carotenoids production. Flow cytometry was successfully used to monitor the yeast cell membrane integrity. Abstract: In this study, secondary brewery wastewater (SBWW) supplemented with sugarcane molasses (SCM) was used for SBWW treatment with concomitant lipid and carotenoid production by the yeast Rhodosporidium toruloides NCYC 921. In order to improve the biomass production, ammonium sulfate, yeast extract and urea were tested as nitrogen sources. Urea was chosen as the best low-cost nitrogen source. A fed-batch cultivation was carried out with SBWW supplemented with 10 g L −1 of sugarcane molasses as carbon source, and 2 g L −1 of urea as nitrogen source. A maximum biomass concentration of 42.5 g L −1 was obtained at t = 126.5 h and the maximum biomass productivity was 0.55 g L −1 h −1 at t = 48.25 h. The maximum lipid content was 29.9 % w/w (DCW) at t = 94 h of cultivation and the maximum carotenoid content was 0.23 mg g −1 at 120 h of cultivation. Relatively to the SBWW treatment, after the batch phase, 45.8 % of total Kjeldahl nitrogen removal, 81.7 % of COD removal and 100 % of sugar consumption were observed. Flow cytometry analysis revealed that 27.27 % of the cells had injured membrane after the inoculation. This proportion was reduced to 10.37 % at the end of the cultivation, indicating that cells adapted to the growth conditions.